1977
DOI: 10.1042/bj1620359
|View full text |Cite
|
Sign up to set email alerts
|

Binding of magnesium ions to cell walls of Bacillus subtilis W23 containing teichoic acid or teichuronic acid

Abstract: When grown in a chemostat under various nutritional conditions, cells of Bacillus subtilis W23 produce walls containing teichoic acid or teichuronic acid. The binding of Mg2+ to these walls and to the isolated anionic polymers in solution was measured by equilibrium dialysis. In solution the ribitol teichoic acid bound Mg2+ in the molar ratio Mg2+/P=1:1 with an apparent association constant (Kassoc.) of 0.61 X 10(3)M-1, and the teichuronic acid bound Mg2+ in the ratio Mg2+/CO2-=1.1, Kassoc.=0.3 X 10(3)M-1. Cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…From a series of covalent modifications of walls from B. subtilis 168, it was concluded that while both TA and peptidoglycan each contribute sites for binding metal cations, the latter would appear to provide a larger fraction (55,131,324,453). In contrast, Heckels et al (212) found that the WTA provides the larger fraction of anionic binding sites in B. subtilis W23, an organism with poly(Rbo-P) WTA. WTA and teichuronic acids are the prime sites of metal binding in B. licheniformis (52).…”
Section: D-alanyl Esters In the Binding Of Ligandsmentioning
confidence: 97%
“…From a series of covalent modifications of walls from B. subtilis 168, it was concluded that while both TA and peptidoglycan each contribute sites for binding metal cations, the latter would appear to provide a larger fraction (55,131,324,453). In contrast, Heckels et al (212) found that the WTA provides the larger fraction of anionic binding sites in B. subtilis W23, an organism with poly(Rbo-P) WTA. WTA and teichuronic acids are the prime sites of metal binding in B. licheniformis (52).…”
Section: D-alanyl Esters In the Binding Of Ligandsmentioning
confidence: 97%
“…186, 2004 TEICHOIC ACID IS ESSENTIAL UNDER PHOSPHATE LIMITATION 7871 teichoic acid. The two polymers have been shown to bind magnesium ions with nearly identical affinities (19) and to regulate autolysins by a proton motive force (10). However, teichoic acid may play a unique role that teichuronic acid cannot play.…”
Section: Discussionmentioning
confidence: 99%
“…Various functions of wall teichoic acid have been proposed, and many of them are related to its anionic character, such as cell shape maintenance by charge repulsion (34) or buffering of magnesium ions (19). However, the ability of teichoic acid to act as a phosphate reservoir appears to present an exception to its indispensability.…”
mentioning
confidence: 99%
“…A small but significant portion of some metals accumulated in active cyanobacteria is concentrated inside the cell (Baxter and Jensen, 1980;Jensen et al, 1982Jensen et al, , 1986Pettersson et al, 1985aPettersson et al, , 1988Rachlin et al, 1984;Singh et al, 1992Singh et al, , 1993. In contrast, for many other species, cell wall accumulation is the only significant form of sequestration (Beveridge and Fyfe, 1985;Heckels et al, 1977;Hoyle and Beveridge, 1984;Macaskie, 1990;Macaskie et al, 1987).…”
Section: Introductionmentioning
confidence: 92%